A Tale of Income and Energy in Rural Areas: What Contributes to People's Happiness? Evidence from Eastern Indonesia - Tasik, Hizkia H. D. (International Journal of Energy Economics and Policy, 2019)
Cash transfers and energy subsidies are two striking programs of the Indonesian government to improve the welfare of poor people. These programs have been in effect for years and altered over time. However, it is unclear that the alterations end up having utility at least at the same level as pre-alteration level. Without a good knowledge on the relative importance of the programs, one may find difficulties in assessing the utility level before and after the alteration. To my knowledge this is the first study to describe the relative importance of income and energy spending where the change may be affected by cash transfers and energy subsidies. The relative importance is anchored at the individual's happiness level as the proxy of the utility level. This study relies on a survey covering 345 respondents residing in rural areas of North Sulawesi Province, Indonesia and cross-section regression models. The findings suggest that every rupiah spent on energy has bigger impacts on happiness improvement than every rupiah received as income. Programs that increase energy consumption may be more important than programs that boost income of people living in rural areas where most poor people are located. Therefore, alteration in one program that can create loss in utility must be compensated by another program that can create gain in utility at least at equal amount, otherwise the alteration is not a pro-poor. Keywords: Cash Transfers; Energy Subsidy; Rural Individuals; Happiness JEL Classifications: I32, H53 DOI: https://doi.org/10.32479/ijeep.7782